Mineralogical analysis of 14 PHAs from ViNOS data. Issue 2 (2nd December 2022) - Morate, D; Popescu, M; Licandro, J; Tinaut-Ruano, F; Tatsumi, E; de León, J
ABSTRACT: Potentially hazardous asteroids (PHAs) are objects that can have close encounters with Earth and are significantly large to cause significant regional damage in the event of impact. The mitigation strategy requires to understand their physical properties. We aim to investigate the physical nature of PHAs, using data obtained within the framework of the Visible NEOs Observations Survey (ViNOS). We analysed and characterized a sample comprised of 14 of these objects. To conduct this study, we obtained visible spectra of 14 PHAs in the 0.5–0.9-μm region using the 2.5 m Nordic Optical Telescope, located at the El Roque De Los Muchachos Observatory in La Palma (Spain). The resulting spectra were combined with their corresponding near-infrared counterparts, available in the literature from the Small Main-Belt Asteroid Spectroscopic Survey (SMASS). We performed a taxonomical classification, computed several diagnostic spectral parameters (slopes, band centres, and band area ratios), and provide completely new mineralogical information for 10 of these objects. We also compared the data with laboratory spectra of meteorites from the RELAB data base. Among the studied sample of PHAs, approximately 90 per cent of the objects (13 out of 14) were classified as silicaceous (S-types and subclasses). Only one object, 489 486, was classified as carbonaceous. Five of the studied PHAs did not have previous taxonomic classifications. The comparisons of the silicaceous PHAs with meteoritic spectra yielded, in all cases, ordinary chondrites as the best match for meteoritic analogues. The computed mineralogy of all of our targets is also consistent with this results.